Land and Building Tax Calculation Application (E-PBB): Case Study in One of The Villages in West Java - Rifka Fitriyah; Rinawati Rinawati (Electronic, Business, Management and Technology Journal, 2023)
Introducing an efficient land and building tax computation system can have favorable outcomes for the rural community and its inhabitants. The management and authenticity of data about the distribution of Property Tax Notification Letters (SPPT) have historically posed issues within the tax management process. The e-PBB program for calculating land and building taxes in the Tribaktimulya Village case study is implemented as a web-based platform. The application utilizes quantitative data collection methods, including observation, interviews, and literature reading. The system is developed with the Object-Oriented Analysis and Design (OOAD) methodology, which encompasses the stages of analysis, design, and system implementation centered around objects. The design of this system is anticipated to enhance the ability of village authorities to input and compute land and building taxes that are either outstanding or paid. Automating the calculation process will enhance efficiency while simplifying tax report generation will contribute to a more effective and streamlined operational workflow.